ANANLYSIS OF SIXTH SEMESTER STUDENTSâ PERCEPTION TOWARD MICROTEACHING IN THE CONTEXT CURRICULUM 2013 IN ENGLISH LANGUAGE EDUCATION - Hartawati, K.M N; Sudirman, Sudirman; Adnyani, L.D.S (Universitas Pendidikan Ganesha, 2018)
This study aimed to describe the sixth semester students perception toward microteaching in the context of curriculum 2013 in English Language Education, Undiksha in academic years 2018/2019.This research used mix method design. the subject of this research was 87 sixth semester students and the object of this research was students perception toward microteaching in the context of curriculum 2013. The data obtained through questioner and interview sheet.Â The result of data showed that students gave positive responds to the questionnaire about sixth semester studentsâ perception toward microteaching subject in the context of curriculum 2013. It was proven from the calculation of the score was 70% which means it is above 60%. It means that students gave positive responds to the questionnaire about sixth semester studentsâ perception toward microteaching subject in the context of curriculum 2013.Keywords: perception, microteaching, curriculum 2013.